Stitching Stories - The art of embroidery in Gujarat - Nina Sabnani; Kala Raksha (Trust : Kachchh, India) (Chennai : Tulika Publishers, 2011)
Adaptation of Tanko bole chhe, an animation documentary film for children.
Grade - 2
Keywords: Migration; PY UOI - Where we are in place and time/Arts -- Non fiction/PY UOI - Where we are in place and time/Arts; Arts Stories -- Arts Stories; Culture -- Culture; Beliefs And Values -- Beliefs And Values; Migration -- Migration; Biography -- Biography